Impoliteness Strategies In The Third Indonesia Presidential Debate 2024: Pragmatics Research - Hana Maria Simanjuntak; Ervina CM Simatupang (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
This research examines the impoliteness strategies employed during the third Indonesian Presidential Debate of 2024 from a pragmatic perspective. Using Jonathan Culpeper's theories of impoliteness (1996, 2011) as a theoretical framework, the research aims to identify and analyze the types of impoliteness strategies used by presidential candidates and determine their functions within the debate context. The research utilizes a descriptive qualitative method, with data collected from the Kompas TV YouTube channel's broadcast of the debate. The research focuses on identifying instances of bald-on-record impoliteness, positive impoliteness, negative impoliteness, sarcasm/mock politeness, and withhold politeness. Additionally, it examines whether these strategies serve affective, coercive, or entertaining functions. Preliminary analysis reveals the presence of four types of impoliteness strategies: bald-on-record, positive impoliteness, negative impoliteness, and sarcasm. Notably, bald-on-record impoliteness emerged as the most frequently used strategy, while no instances of withhold politeness were observed. The affective function was found to be the most prevalent, suggesting that candidates often employ impoliteness to express emotions and influence audience perceptions. This research contributes to the field of pragmatics by providing insights into language use in high-stakes political contexts. It also offers a deeper understanding of how impoliteness strategies can impact public perception and the democratic process in Indonesia. The findings may serve as a valuable resource for future studies on political discourse and communication strategies in presidential debates.